Monitoring and guidance of high intensity focused ultrasound exposures in real time using acousto-optic imaging: feasibility and demonstration ex vivo - Lai, P; McLaughlan, J; Draudt, A; Murray, T; Cleveland, R; Roy, R (Society of Photo-optical Instrumentation Engineers, 2010)
High intensity focused ultrasound (HIFU) is a powerful noninvasive tool for targeted tissue ablation. Monitoring of the treatment process and efficacy in real time, however, remains challenging. The tissue necrosis during the HIFU exposure leads to changes in optical absorption and scattering coefficients. In this paper, we explore the use of acousto-optic imaging (AOI), a hybrid technique that combines ultrasound with diffuse light to obtain deep-tissue optical contrast at ultrasound resolution, to sense the changes in optical contrast at depth in tissue associated with the onset formation and development of the necrosed tissue region. In this technique, the tissue to be treated is illuminated with near-infrared light and a continuous, amplitude-modulated focused ultrasound beam is used to induce thermal tissue necrosis as well as the acousto-optic (AO) interaction. The AOI signal is detected via a photorefractive crystal (PRC)-based interferometer, and then fed into a lock-in amplifier tuned to the ultrasound modulation frequency. As a thermal lesion forms in the ultrasound focal zone, which is also the zone of AO interaction, the AOI signal diminishes in amplitude owing to enhanced optical attenuation. It is further shown that the reduction of the AOI signal is correlated with the volume of ensuing lesion. Therefore, the evolution of AOI signal as a function of time provides a means for continuous monitoring of HIFU treatment process as well as exposure guidance.